Fibroblast growth factors-5 and -9 distinctly regulate expression and function of the gap junction protein connexin43 in cultured astroglial cells from different brain regions - Reuss, Bernhard; Unsicker, Klaus (Glia, 2000)
Astroglial cells contribute to neuronal maintenance and function in the normal and diseased brain. Gap junctions formed predominantly by connexin43 (cx43) provide important pathways to coordinate astroglial responses. We have previously shown that fibroblast growth factor (FGF)-2, which occurs ubiquitously in the CNS, downregulates gap junction communication in cortical and striatal, but not in mesencephalic astroglial cells in vitro (Reuss et al. Glia 22:19-30, 1998). Other members of the FGF family expressed in the CNS include FGF-5 and FGF-9. We show that both FGF-5 and FGF-9, like FGF-2, downregulate astroglial gap junctions and functional coupling. However, their effects are strikingly different from different brain regions, with regard to astroglial cells. FGF-5 specifically affects mesencephalic astroglial cells without changing coupling of cortical and striatal astroglia, while FGF-9 reduces gap junctional coupling in astroglia from all three brain regions. Both cx43 mRNA and protein levels as well as functional coupling assessed by dye spreading are affected. To clarify whether brain region-specific effects of FGFs on astroglial coupling are due to differential expression of FGF receptors (FGFR), we monitored expression of the four known FGFR mRNAs in astroglial cultures by RT-PCR. Irrespective of their regional origin, astroglial cells express mRNAs for FGFR-2 and FGFR-3. In summary, our results provide evidence for an important role of FGF-2, -5, and -9 in a distinct, CNS region-specific regulation mechanism of astroglial gap junction communication. The molecular basis underlying the regionally distinct responsiveness of astrocytes to different FGFs may be sought beyond distinct FGFR expression. GLIA 30:231-241, 2000. © 2000 Wiley-Liss, Inc.
Gesehen am 24.11.2016